Isotopic evidence for changing mobility and landscape use patterns between the Neolithic and Early Bronze Age in western Ireland. (April 2020) - Snoeck, Christophe; Jones, Carleton; Pouncett, John; Goderis, Steven; Claeys, Philippe; Mattielli, Nadine; Zazzo, Antoine; Reimer, Paula J.; Lee-Thorp, Julia A.; Schulting, Rick J.
Highlights: Mulit-isotope (C, O, Sr) analyses of both un- and cremated human remains. Uncremated and cremated individuals used different parts of the landscape. All cremated individuals appear to be 'non-locals'. Radiocarbon dates show re-use of the court tomb of Parknabinnia during the BA. Both un- and cremated human remains should be analysed when present together. Abstract: This paper presents the results of a study using strontium, oxygen and carbon isotopes, strontium concentrations, infrared analyses and radiocarbon dating to investigate human mobility and landscape use as seen in individuals from the Neolithic court tomb of Parknabinnia, Co. Clare, Ireland. Taking advantage of the recent demonstration that it is possible to obtain reliable in vivo strontium isotope signals from calcined bone, we compare measurements on cremated bone (n = 4) and uncremated tooth enamel (n = 4). The results suggest that two out of four uncremated enamel samples can be considered 'local' while the other two, and all four cremated bone samples, represent 'non-local' individuals. New radiocarbon dates obtained on two of the cremated bone fragments place them in the Chalcolithic/Early Bronze Age, contrasting with the Neolithic dates previously obtained on the uncremated remains, demonstrating re-use of the monument. Assuming that our small sample is representative, it seems that the court tomb was used for burial by both 'locals' and 'non-locals' during the Neolithic and predominantly by 'non-locals' in the Chalcolithic/Early Bronze Age. This stands in contrast to the nearby Early Neolithic portal tomb of Poulnabrone where only one individual (of 17 analysed) appears to be an 'outsider'. Our results suggest that, even within a small region, mobility and landscape use may have differed significantly within the Neolithic and also between the Neolithic and the Chalcolithic/Early Bronze Age.